Evaluation of mixed frequency approaches for tracking near-term economic developments in North Macedonia - Gani Ramadani; Magdalena Petrovska; Vesna Bucevska (National Bank of the Republic of North Macedonia, 2021)
Aggregate demand forecasting, also known as nowcasting when it applies to current quarter assessment, is of notable interest to policy makers. This paper concentrates on the empirical methods dealing with mixed-frequency data. In particular, it focuses on the MIDAS approach and its later extension, the Bayesian MF-VAR. The two strategies are evaluated in terms of their accuracy to nowcast Macedonian GDP growth, using same monthly frequency data set. The results of this study indicate that the MIDAS regressions demonstrate comparable forecasting performance to that of MF-VAR model. Moreover, it is interesting to note that the two approaches are reciprocal, since in general, their combined forecast demonstrates clear superiority in predicting business cycle turning points. Additionally, the MF-VAR model showed higher precision in times of increased uncertainty
Keywords: E37; C53; 330; MF-VAR; Bayesian estimation; MIDAS; Forecast pooling; Forecast evaluation